The thin man goes home - Thorpe, Richard, 1896-1991; Riskin, Robert; Taylor, Dwight; Kurnitz, Harry; Powell, William, 1892-1984; Loy, Myrna, 1905-1993; Watson, Lucile, 1879-1962.; Snell, David, 1897-1967; Metro-Goldwyn-Mayer.; Loew's Incorporated; Turner Entertainment Co.; Warner Home Video (Firm) (Burbank, CA : Turner Entertainment Co., 2005)
When detectives Nick and Nora Charles visit his parents, they solve the murder of a man who drops dead on their porch.
Based upon characters created by Dashiell Hammett.
Originally released as a motion picture in 1941.
Features: Robert Benchley comedy short "Why daddy?" classic cartoon "Screwball squirrel," theatrical trailer, scene selection, interactive menus.
Directors of photography, Karl Freund ; art directors, Cedric Gibbons, Edward Carfagno ; film editor, Ralph E. Winters ; music, David Snell.
William Powell, Myrna Loy, Lucille Watson, Gloria DeHaven, Anne Revere, Helen Vinson, Harry Davenport, Leon Ames, Donald Meek, Edward Brophy.
MPAA rating: Not rated.
Keywords: Hammett, Dashiell, -- 1894-1961 -- Film and video adaptations; Charles, Nick (Fictitious character) -- Drama; Charles, Nora (Fictitious character) -- Drama; Detective and mystery films; Video recordings for the hearing impaired; Based on the book; Feature films; Detective films; Mystery films